2013
DOI: 10.18632/oncotarget.1425
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor potential of Interleukin-27 in prostate cancer

Abstract: Prostate cancer (PCa) is of increasing significance worldwide as a consequence of the population ageing. Fragile elderly patients may particularly benefit from noninvasive and well tolerable immunotherapeutic approaches. Preclinical studies have revealed that the immune-regulatory cytokine IL-27 may exert anti-tumor activities in a variety of tumor types without discernable toxicity. We, thus, investigated whether IL-27 may function as anti-tumor agent in human (h) PCa and analyzed the rationale for its clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…In prostate tissue from patients, WSX-1 was expressed by normal epithelia and in prostate cancer the expression of WSX-1 was lost during development of the tumors. However, in early stages IL-27 reduced proliferation and vascularization and had also an immune-stimulatory effect on the tumor microenvironment which might even be beneficial for patients with late stage tumors [69].…”
Section: Chronic Inflammation and Cancermentioning
confidence: 99%
“…In prostate tissue from patients, WSX-1 was expressed by normal epithelia and in prostate cancer the expression of WSX-1 was lost during development of the tumors. However, in early stages IL-27 reduced proliferation and vascularization and had also an immune-stimulatory effect on the tumor microenvironment which might even be beneficial for patients with late stage tumors [69].…”
Section: Chronic Inflammation and Cancermentioning
confidence: 99%
“…Recently, IL-27 was proven to possess multifaceted anti-tumor activity in lung (15), prostate (16), pancreatic (17) and breast cancers (18). In addition, IL-27 has been reported to possess potent antiangiogenic activity (19).…”
Section: Introductionmentioning
confidence: 99%
“…In tumor models, IL‐27/WSX‐1 signaling plays both protumor and antitumor effects through both generation and exhaustion of cytotoxic T lymphocyte (CTL), together with suppression of DC function . In addition, several studies reported that IL‐27 secreted by tumor cells also have antiangiogenic activity .…”
Section: Introductionmentioning
confidence: 99%